Durability of the two-lumen catheter in hemodialysis patients; Ethanol 70%-heparin versus cefazolin-heparin: a randomized, double-blind clinical trial study - Hadi Yousefi; Mehdi Hosseinifard; Mojgan Falaki; Fariba Asadi Noghabi; Hamidreza Samimagham; Mohsen Yousefi; Hossein Mardanparvar; Jahanbakhsh Vahdatnejad (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Maintenance of hemodialysis catheters is essential for the patients and medical staff due to their repeated use for hemodialysis and other therapeutic interventions in the hospital. Objectives: This study aimed to comprise the effect of ethanol 70%-heparin versus cefazolin-heparin on the catheter durability time of hemodialysis patients. Patients and Methods: The study population consisted of 73 hemodialysis patients referred to Shahid Mohammadi hospital in Bandar Abbas. Patients were divided into two groups cefazolin (cefazolin 5 mg/dL, and heparin 2500 IU/mL) and ethanol (ethanol 70%, and heparin 2500 IU/mL). In both groups, after each hemodialysis session, 2.9 to 3.3 mL of the locking solution was locked in the catheter lumen and remained until the next session. This intervention was conducted for all patients continuously for five months. The time of catheter durability was calculated from the time of catheter placement in the central vein until the time that it has been taken out according to the doctor's diagnosis. Data were collected and analyzed by SPSS version 26. Results: Results showed that demographic characteristics, including age, weight, gender, marital status, catheter type, underlying diseases, and dialysis adequacy between the two groups were similar (P>0.05). In the ethanol group, the mean time of the catheter durability was 27.5 days, and in the cefazolin group was 26.98 days. Although the time of the catheter durability was slightly higher in the ethanol group, this difference was not significant (P=0.194). Conclusion: Cefazolin and ethanol 70% did not show a significant difference in the catheter durability time of hemodialysis patients. Trial Registration: The trial protocol was approved by the Iranian Registry of Clinical Trials (IRCT20210811052145N1; https://en.irct.ir/trial/58037, ethical code; IR.HUNS.REC.1398.052).